The Influence of Service Quality on Patient Satisfaction at Selayang Hospital, Selangor - SITI NORZIAH ISMAIL,; Nur Anis Misya, (Research in Management of Technology and Business, 2023)
Nowadays it is quite difficult to meet patient satisfaction in hospitals. This is because poor service from healthcare and defect in Selayang hospital building make the healthcare industry in increasingly becoming more competitive to fulfil patient satisfaction. This study aims to know what relationship service quality on patient satisfaction. Using a structured questionnaire, data were gathered from 208 patient who receive treatment and had experience treatment at Selayang Hospital. This questionnaire was distributed through social media which is WhatsApp and Instagram. The result shows that all the dimension service quality is significance which can fulfil patient satisfaction. However, social responsibility was the important toward patient at Selayang Hospital. The implication is that to keep patient satisfied, the hospital must invest more or training their healthcare service to make improvement.